The importance of nongovernmental organizations (NGOs) in global governance and value creation: an international business research agenda - Teegen, Hildy; Doh, Jonathan P; Vachani, Sushil (Journal of International Business Studies, 2004)
The emergence of organized civil society and of nongovernmental organizations (NGOs) as organizational manifestations of broader social movements has dramatically altered the global political–economic landscape. The increasing global reach of NGOs challenges established international business (IB) research, and highlights opportunities for broadening and adapting extant paradigms in the field. In this article, we introduce the concept of NGOs and contrast them with their private-sector (firm) and public-sector (government) counterparts within the context of IB. We discuss factors giving rise to NGOs as important organizational entities that participate in global value creation and governance, and identify limits to their efficacy and viability. We identify important questions raised by incorporating NGOs into our conceptualization of global context, and we challenge three basic tenets of IB theory: the definition and dynamics of an institutional field, the relevance/centrality of a firm–government (i.e., two-sector) bargaining model, and the pre-eminence of the firm as the global organization of interest within the field. We conclude by offering suggested research directions that should serve as catalysts for this new and potentially rich area of future IB research.